AI-POWERED SMART TECHNOLOGIES FOR ENHANCING INNOVATIVE ENGLISH TEACHING IN HIGHER EDUCATION IN KAZAKHSTAN - Meiramova, S.A.; S.B. Zagatova (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The development of foreign language teaching methodologies in the context of an evolving educational landscape is directly linked to the continuous integration of Artificial Intelligence (AI) in various fields. The integration of AI-driven tools and technologies has reshaped communication and educational experiences by creating opportunities for innovative pedagogical approaches in higher education in Kazakhstan. This paper explores the use of AI-powered smart technologies in English language learning and teaching, emphasizing their role in interactive educational activities, personalized learning environments, and critical thinking development among students at A.K. Kussayinov Eurasian Humanities Institute in Kazakhstan. Method used: Literature analysis, pedagogical experiment and students’ feedback to assess the impact of AI-driven applications on English learning in a controlled setting and understand students’ perceptions and motivation along with exploring existing research on AI-based approaches in education. Results showed that (1) the use of AI-driven smart technologies in English teaching significantly enhances the learning process. Students in experimental group, who used personalized AI-supported mobile applications, demonstrated improved engagement, motivation, and autonomy compared to the control group; (2) the increase of students’ interest in using smartphones for educational purposes and a positive attitude towards AI-assisted learning; (3) the effectiveness of AI-based personalization confirmation in enhancing better language acquisition outcomes. Novelty lies in (1) the integrated application of AI-driven smart technologies to create personalized learning environments in English learning and teaching at the institute level; (2) offering a practical model for implementing AI innovations in language education, particularly within the context of Kazakhstan’s higher education system.